2023
DOI: 10.18178/ijiet.2023.13.1.1784
|View full text |Cite
|
Sign up to set email alerts
|

The Physics Classroom in an Online 3D Virtual World: A Thai High School Teacher Needs Analysis

Abstract: The study set out to examine the actual and desired needs of Thai high school physics teachers in the 2021 academic year from a sample of 44 teachers in Thailand’s northeastern Surin Province. Also, assessment was undertaken concerning each teacher’s ‘order of needs’ from the 41 items presented for evaluation to the teachers. Moreover, there were three main categories in the study’s assessments. These were the teachers’ opinions on the use of 3-dimension virtual learning (3DVL) teaching media in physics for, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Various learning models and methods have been developed to achieve learning motivation. Often cited studies include flipped classrooms, blended learning, problem-based learning (Srakaew et al, 2021), project-based learning (Lee & Yuan, 2018), gamification (Chinchua et al, 2022;Kummanee et al, 2020;Poondej & Lerdpornkulrat, 2019;Sarapak et al, 2022), and online/e-learning (Poondej & Lerdpornkulrat, 2019;Yee, 2015;Yustika & Iswati, 2020).…”
Section: Innovative Training Course (Itc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Various learning models and methods have been developed to achieve learning motivation. Often cited studies include flipped classrooms, blended learning, problem-based learning (Srakaew et al, 2021), project-based learning (Lee & Yuan, 2018), gamification (Chinchua et al, 2022;Kummanee et al, 2020;Poondej & Lerdpornkulrat, 2019;Sarapak et al, 2022), and online/e-learning (Poondej & Lerdpornkulrat, 2019;Yee, 2015;Yustika & Iswati, 2020).…”
Section: Innovative Training Course (Itc)mentioning
confidence: 99%
“…It has also been suggested that in some classroom environments, such as physics, where laboratories are expensive, potentially dangerous, or non-existent, virtual reality (VR) can be a method to supplement 'hands-on' learning (Sarapak et al, 2022). In a similar manner where patient wellness is at stake, VR has been suggested to train health care professionals (Bracq et al, 2019;Khan et al, 2018).…”
Section: Innovative Training Course (Itc)mentioning
confidence: 99%
“…Multisensory instruction incorporates multiple senses in teaching and learning activities to enhance comprehension and retention. This can involve using visual aids, hands-on activities, audiovisual materials, and interactive technologies such as gamification and virtual realities (VR) to engage students and reinforce learning (Poondej & Lerdpornkulrat, 2019;Sarapak et al, 2022).…”
Section: Multisensory Instructionmentioning
confidence: 99%
“…Newer pedagogies that have also been identified as being particularly effective or being frequently explored in online learning are the flipped classroom, blended learning, problem-based learning (Srakaew et al, 2021), and gamification (Sarapak et al, 2022).…”
Section: The Tdpld Program's Performance In Terms Of Teacher Developm...mentioning
confidence: 99%